DAMPAK UU CIPTA KERJA TERHADAP PEMUTUSAN HUBUNGAN KERJA ATAS EFESIENSI PERUSAHAAN - Zulfikar, Ahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The purpose of this study is to determine the implementation of the Job Creation Law on its impact on termination of employment due to company efficiency and how the rights of workers who experience termination of employment on company efficiency after the implementation of the Job Creation Law. The method used in this study is normative research, namely research whose main object of study is statutory regulatory documents and library materials. The impact of the Job Creation Law on termination of employment on company efficiency is a change between Law Number 13 of 2003 concerning Manpower and Law Number 6 of 2023 concerning Job Creation in terms of termination of employment by the company, employers are required to provide severance pay, long service awards and replacement rights. The aim of efficiency is to prevent losses or companies from experiencing company losses. However, on the other hand, the rights of workers who are laid off on the grounds of company efficiency have certainly changed and there are fewer provisions for calculating severance pay which only leaves 0.5 Provisions. In preventing termination of employment, a dialogue must first be conducted to establish a perception of the efficiency plan as employers strive to prevent layoffs. Termination of employment is the last step taken by employers if no agreement is reached in the dialogue between Workers, Labor Unions and Employers.Keywords: Impact of the Job Creation Law, Termination of Employment, Company Efficiency.